The problems and prospects of cardphone in Malaysia - Mohd. Sidek, Fawziah; Ebrahim, Abd. Rahman; Jubaidi, Asha'ari; Masari, Madaruddin (1990)
The aim of this research is to study the problems and prospects of cardphone in Malaysia. Cardphone was introduced in Malaysia in the year 1990. This system is being operated by Telekom Malaysia and Uniphone Sdn. Bhd. The purpose of introducing cardphones in Malaysia is to give the subscribers the convenience of making calls without having to carry large amount of coins and also to minimise vandalism. Thus, the objectives of this study is to determine the attitudes and perceptions of the cardphone users, the reliability, problems encountered and how it has helped to improve the public telephone services.